2017
DOI: 10.6002/ect.2016.0099
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Many investigations on surgical methods and medical treatment are currently done on pigs. This is possible because the pig is sufficiently close genetically to humans. In recent years, progress in liver surgery has opened new possibilities in surgical treatment of liver diseases. Because the methods are relatively novel, various improvements are still needed, and it is thus helpful to conduct experimental surgeries on pig livers. We reviewed the literature to compare the anatomic and functional features of pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 39 The arterial vasculature of pig liver was reported to have great similarity with the human liver system. 41 Although our results demonstrated proof-of-concept using an in vitro, ex vivo, and an in vivo pig model, the above findings suggested that our in vivo study had limitations in terms of species differences, which influenced the blood diameter, thickness, and other structures on light transmittance.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“… 39 The arterial vasculature of pig liver was reported to have great similarity with the human liver system. 41 Although our results demonstrated proof-of-concept using an in vitro, ex vivo, and an in vivo pig model, the above findings suggested that our in vivo study had limitations in terms of species differences, which influenced the blood diameter, thickness, and other structures on light transmittance.…”
Section: Discussionmentioning
confidence: 54%
“…Species differences in blood vessel properties between humans and pigs have been investigated. 38 , 39 , 40 , 41 Significant differences in aorta thickness have been identified between humans and pigs; the ascending aorta, the left and right coronary sinus, and the noncoronary sinus of the porcine heart were thicker than the respective human samples. 38 The blood diameters of both the right and left main renal arteries in the pig were examined and were found to be equivalent to humans; however, there were differences in the branching angle.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed study in the cynomolgus monkey ( Macaca fasciularis ) described four lobes as in rodents ( Vons et al, 2009 ). Despite differences in external appearance, the same internal segmentation is consistent between species ( Kogure et al, 1999 ; Nykonenko, Vávra & Zonča, 2017 ).…”
Section: Survey Methodologymentioning
confidence: 82%
“…Livers of other commonly used experimental animals are similarly lobulated ( Vons et al, 2009 ; Nykonenko, Vávra & Zonča, 2017 ; Stan, 2018 ). Nomenclature used is also similar to rodents.…”
Section: Survey Methodologymentioning
confidence: 99%
“… 7 , 25 , 29–32 In addition to possessing the potential to generate a large variety of analogous cells, tissues, and organs, cells produced through blastocyst complementation are also immunocompatible, reducing the risk of rejection in the recipient species following transplantation. 33 , 34 …”
Section: Introductionmentioning
confidence: 99%